EPISTEMOLOGI PEMIKIRAN ISLAM ‘ABED AL-JABIRI DAN IMPLIKASINYA BAGI PEMIKIRAN KEISLAMAN - Nurfitriani Hayati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
Religious issue that appearing in Arab society and how they give attention to their tradition or Turâts has made them overly glorifies the glories of the part and become retarded in the face of modernity. So the Issue has motivated Al-Jabiri to offer his idea. He pins down critically from what we call or reputed by “reference” and “how to refer to”. Abed al-Jabiri is one of Muslim philosopher and becomes one of the leading Islamic Arab thinker about tradition relevance in the modern era. He describes that today what we need is combination between “critical of the past era” in order to avoid from history manipulation and “critical today” in order to disappear the identity confirmation and the apology within confront every west concept or idea. Therefore, to find out more his epistemology concept about Islam thought also his thought implication for Islam, this paper examines al-Jabiri’s thought by critical analysis with library research method. The result of this paper makes the point that in reviewing and critiquing a tradition, Al-Jabiri uses of